2006
DOI: 10.1542/peds.2006-0272
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Flow Velocimetry in the Superior Mesenteric Artery on the First Day of Life in Preterm Infants and the Risk of Neonatal Necrotizing Enterocolitis

Abstract: We concluded that neonates with high resistance patterns of blood flow velocity in the superior mesenteric artery on the first day of life are at increased risk of developing necrotizing enterocolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 13 publications
5
54
3
Order By: Relevance
“…The changes observed on the first day of life most likely represent persistence of these fetal redistribution patterns into postnatal life, as stated in the study by Campbell et al [16] In this study, the patterns of Doppler flow indices indicating increased resistance in the SMA were associated with an increased risk of NEC. This finding was in accordance with those of Murdoch et al [14], who suggested that splanchnic flow was compromised immediately after birth in many infants who went on to develop NEC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The changes observed on the first day of life most likely represent persistence of these fetal redistribution patterns into postnatal life, as stated in the study by Campbell et al [16] In this study, the patterns of Doppler flow indices indicating increased resistance in the SMA were associated with an increased risk of NEC. This finding was in accordance with those of Murdoch et al [14], who suggested that splanchnic flow was compromised immediately after birth in many infants who went on to develop NEC.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that high resistance to flow in the SMA was associated with a delay in establishing feeding and those infants with risk factors for NEC tended to have higher resistance patterns of flow in the SMA. [8,14] In this study, twelve neonates (23%) developed NEC, which is a relatively high incidence of NEC and could be explained by most studied neonates who developed NEC having extremely low birth weights (<1000 g); this finding was in accordance with those of Kliegman et al [15], who stated that among infants with very low birth weights (VLBW, <1500 g), the incidence might be as high as 15%, with a mortality rate of 10-30%.…”
Section: Discussionmentioning
confidence: 99%
“…CAF:LVO was lower in infants with adverse outcomes. Although this did not reach statistical significance possibly due to small numbers, it may explain the association between PDA and necrotizing enterocolitis, IVH and death [16,17] . LA:Ao was significantly higher in infants with IVH, and DAo EDV was lower in infants that died, and those requiring ventilation on day 3.…”
Section: Discussionmentioning
confidence: 74%
“…The significant reduction in the SMA EDV in the NEC cases in our study matched that in Murdoch et al's study, which found that the risk of NEC significantly decreased with the rise in the end-diastolic flow velocity and that infants who developed NEC later in the neonatal period had a high resistance pattern in the SMA, or the celiac artery, on their first day of life. That may be attributed to the fact that the vasoconstriction of the circulation in neonatal life has a role in the etiology of NEC [22]. Few of our patients had received enteral feeding at any stage in their lives.…”
Section: Discussionmentioning
confidence: 93%